The first principal study of decorated hexagonal boron nitride nanosheets with Ni and Pd atoms as drug carrier - Ziming Wang; Yu Wan; Hongxia Li; Yi Wang (Ain Shams Engineering Journal, 2024)
Development of advanced materials for drug delivery is of great importance for efficient cancer therapy. Among various materials for drug delivery, boron nitride has attracted much attention due to its unique properties for pharmaceutical applications. The efficiency of pure boron nitride nanosheets (BNNS) and modified BNNS by Ni and Pd atoms in the delivery process of the anticancer medicine 5-fluorouracil (5-FU) is studied here within the framework of density functional theory (DFT) method in different configurations. The computational method was carried out for better understanding the new drug delivery system design and release of drug. Calculation of the adsorption energy revealed that adsorption of drug via the F atom in the perpendicular configuration was more desirable than adsorption in the perpendicular state via the O atom of the drug molecule. On the other hand, Ni and Pd improved the geometry and electronic properties of the adsorption process. The Eads increased from −3.488 for pristine BNNS to −7.365 and −8.287 eV for Ni@BNNS and Pd@BNNS, respectively. The electronic band structures demonstrated the competency of the modified BNNS for adsorption of 5-FU medicine via change in the VBM, CBM, and Egap values prior and after the molecules are adsorbed onto the surface.